Quantitative analysis of runoff parameters in selected river basins of Kerala - JJayasree S (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 1990)
The evolution of a drainage basin is the result of the flow of mass and energy and the resistance of topographical surface. Precipitation is the major source of matter and solar radiation, the source of energy. The stream flow is a function of geomorphological and hydrological factors of the river basin. The objectives of this study were to make a quantitative analysis of the effects of geomorphological and climatic factors on the stream flow and to study the inter – relationships between these factors. The selected river basins were Chaliyar and Kabbani. The specific objective was to express stream flow in terms of morphological factors and rainfall. The river basin was divided in to sub basin, each of which contains a rivergauge station. Morphological factors were measured from the map. Monthly rainfall from all the raingauge stations were collected and the arithmetical average for each sub-basin was computed. The monthly stream flow was also collected. It was found that the morphological factors were interrelated. The number of stream segments of successive order form a decreasing geometric progression whereas the length of stream segments of successive orders form an increasing geometric progression. Confluence ratio is inversely related to stream flow. Elongation and drainage area are highly correlated. A larger value for the confluence ratio indicates a more elongated basin and a lower flood peak. The sub - basins are similar to the form of a rectangle. Area and elongation are the morphological parameters strongly influencing the stream flow. Drainage density and stream frequency are highly correlated. Drainage density gets altered by the land use, vegetal cover, deforestation and urbanization. Drainage density also affect stream flow. Finally, the expressions for drainage area in terms of the main stream length, drainage density in terms of stream frequency and average monthly stream flow contributed by unit area in terms of the average monthly rainfall were obtained. The data used for the final equation was inadequate. The equation may be improved, by increasing the number of rivergauge stations and providing more representative raingauge stations.